Phase II Study Evaluating 2 Dosing Schedules of Oral Foretinib (GSK1363089), cMET/VEGFR2 Inhibitor, in Patients with Metastatic Gastric Cancer - Shah, Manish A.; Wainberg, Zev A.; Catenacci, Daniel V. T.; Hochster, Howard S.; Ford, James; Kunz, Pamela; Lee, Fa-Chyi; Kallender, Howard; Cecchi, Fabiola; Rabe, Daniel C.; Keer, Harold; Martin, Anne-Marie; et al. (PLOS ONE, 2013)
Purpose The receptors for hepatocyte and vascular endothelial cell growth factors (MET and VEGFR2, respectively) are critical oncogenic mediators in gastric adenocarcinoma. The purpose is to examine the safety and efficacy of foretinib, an oral multikinase inhibitor targeting MET, RON, AXL, TIE-2, and VEGFR2 receptors, for the treatment of metastatic gastric adenocarcinoma. Patients and Methods Foretinib safety and tolerability, and objective response rate (ORR) were evaluated in patients using intermittent (240 mg/day, for 5 days every 2 weeks) or daily (80 mg/day) dosing schedules. Thirty evaluable patients were required to achieve alpha = 0.10 and beta = 0.2 to test the alternative hypothesis that single-agent foretinib would result in an ORR of ≥25%. Up to 10 additional patients could be enrolled to ensure at least eight with MET amplification. Correlative studies included tumor MET amplification, MET signaling, pharmacokinetics and plasma biomarkers of foretinib activity. Results From March 2007 until October 2009, 74 patients were enrolled; 74% male; median age, 61 years (range, 25–88); 93% had received prior therapy. Best response was stable disease (SD) in 10 (23%) patients receiving intermittent dosing and five (20%) receiving daily dosing; SD duration was 1.9–7.2 months (median 3.2 months). Of 67 patients with tumor samples, 3 had MET amplification, one of whom had SD. Treatment-related adverse events occurred in 91% of patients. Rates of hypertension (35% vs. 15%) and elevated aspartate aminotransferase (23% vs. 8%) were higher with intermittent dosing. In both patients with high baseline tumor phospho-MET (pMET), the pMET:total MET protein ratio decreased with foretinib treatment. Conclusion These results indicate that few gastric carcinomas are driven solely by MET and VEGFR2, and underscore the diverse molecular oncogenesis of this disease. Despite evidence of MET inhibition by foretinib, single-agent foretinib lacked efficacy in unselected patients with metastatic gastric cancer. Trial Registration ClinicalTrials.gov NCT00725712